Eating behavior and physical activity of senior citizens during the COVID-19 lockdown - Denson M. Liday; Mary Rose C. Liwag (International Journal of Public Health Science (IJPHS), 2021)
A new coronavirus has arisen, causing a pandemic of serious respiratory syndrome in humans. The COVID-19 pandemic has a major effect on human health, resulting in abrupt lifestyle changes, social distances and loneliness at home. The goal of this study was to examine the immediate effect of the pandemic on eating behavior and physical activity among the elderly population aged 60 years and older. Data on the features of the senior citizens' profile, eating habits and physical activity during the lock-up were evaluated and analyzed in this report. In addition, the correlation, key and interaction effects of some of the essential variables in the analysis were also evaluated. The findings of the study revealed a need to promote eating habits that may help to minimize the health inequalities created by eating disorders. Moreover, the synergies between the various determinants of eating habits were found to be deficient. Home restrictions and confinement of the participants also reduced the overall physical activty level of the participants. Income class appeared as a factor on the interaction between eating behavior and physical activity. Recognizing these findings may be significant in developing health promotion programs for older people during the remaining period of quarantine or future ones. There is a need for health education as a response scheme to COVID-19 in low-income settings, and it is essential that approaches are contextually suitable with the vulnerable age group.